Hubungan Status Gizi Terhadap Keluhan Disminore Pada Mahasiswi Universitas Bali Dwipa - Komang Tia Juni Astuti (Jurnal Ilmu Kesehatan dan Gizi, 2025)
Women, especially teenagers, often experience dysmenorrhea during menstruation.  The lower part of the stomach is where this discomfort occurs.  The aim of this research is to find out how dietary status influences dysmenorrhea complaints in Bali Dwipa University students. The quantitative descriptive survey method was used in this research. The research sample obtained using a stratified sampling approach was 30 people from a total population of 43 people. The frequency distribution of each variable was analyzed and the chi square test was used to determine the relationship. Research findings show that nutritional status has an impact on female students' dysmenorrhea symptoms. This research aims to deepen understanding and serve as a guide for further research. Apart from that, it is believed that this research can provide further information which can then provide suggestions regarding solutions related to this problem, especially those related to dysmenorrhea complaints in female students.